ED 05-4 NATRIURETIC PEPTIDES, METABOLIC SYNDROME AND HYPERTENSION: AN INTEGRATED VIEW. (September 2016) - Sarzani, Riccardo
Abstract : Atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) are the cardiac natriuretic peptides (NP), true "cardiometabolic" hormones well known for their renal, endocrine and cardiovascular activities leading to reduced sodium reabsorption and arterial blood pressure. These effects are mainly mediated by the second messenger cGMP that also stimulates lipolysis, mitochondriogenesis and a thermogenic program with potency similar to catecholamines. Two distinct NP receptors modulate the final response to cardiac NP: the cGMP-signaling receptor NPRA and the clearance receptor NPRC. The cellular and systemic effects of NP largely depend upon the ratio of the clearance receptor NPRC to the signaling receptor NPRA, both abundantly expressed in human adipose tissue and adipocytes. Indeed, most of the available data indicate that the total NPRC expression in the body is the main negative modulator of the circulating NP levels and, at cellular level, NPRC is a main silencer of their biological effects. NP are not only 'cleared' from circulation by NPRC, but they are also degraded very quickly by neutral endopeptidase (NEP) and both are increased in obesity. Starving sharply decreases NPRC expression in white and brown adipose tissue and a low-calorie diet in obese hypertensive patients strongly potentiates the clinical and biological effects of infused ANP. Hypocaloric diet also enhances ANP-induced lipolysis in humans, whereas obesity is associated with lower circulating levels of NP. Many studies have linked the genes of NP and their receprtros to hypertension and many population studies have also linked reduced NP levels to obesity and metabolic syndrome. Insulin/glucose are the main factors in adipocytes hypertrophy in many conditions characterized by insulin resistance such as metabolic syndrome. Insulin attenuate lipolysis in adipocytes by inducing NPRC expression, linking the eating pattern to reduced NP activities both on adipose tissue and likely in the entire body, suggesting a NP-mediated link between insulin, insulin resistance, sodium retention, and hypertension.